Kajian Potensi Interaksi Obat pada Pasien Gagal Ginjal Rawat Jalan RS â€œXâ€ Kota Cirebon - Hidayati, Nur Rahmi; Susilo, Rinto; Anggraeni, Mila (Pharmacon: Jurnal Farmasi Indonesia, 2020)
Drug interactions are one of part of Drug Related Problem (DRP) which significantly affect the development patient health. This study aims to determine the characteristics of kidney failure patients (age and genitals), an overview of the number of potential drug interactions, an overview of the types and amounts of other drugs interacting, and the severity of drug interactions in kidney failure patients in the Outpatient of â€œXâ€ Hospital Cirebon City. This study involves 126 patient prescriptions. This type of research is a non-experimental research with descriptive analysis method, and using data collection methods with prospective random sampling technique in the Outpatient of RS â€œXâ€ Cirebon. The results of the research from 126 samples obtained showed that the characteristics of Kidney Failure patients were predominantly male as many as 64 people (50.79%), the most age was in the age range 61-70 years as many as 38 people (30.16%). drug interactions 78 sheets of prescriptions (61.9%), the most severity of drug interactions was the strict / significant monitoring of 128 events (64.65%), the average of drug interactions per prescription sheet was 3 interactions, the type and number of the most interacting drug was furosemide + folic acid with 32 potential interactions (41.02%).